Fault Location on Power Networks - Saha, Murari Mohan. (Power Systems,, 2010)
Electric power systems will always be exposed to the failure of their components. When a fault occurs on a line, it is crucial for the fault location to be identified as accurately as possible, allowing the damage caused by the fault to be repaired quickly before the line is put back into service. Fault Location on Power Lines enables readers to pinpoint the location of a fault on power lines following a disturbance. If a fault location cannot be identified quickly and this causes prolonged line outage during a period of peak load, severe economic losses may occur and reliability of service may be questioned. The growth in size and complexity of power systems has increased the impact of failure to locate a fault and therefore heightened the importance of fault location research studies, attracting widespread attention among researchers in recent years. Fault location cannot be truly understood, applied, set, tested and analysed without a deep and detailed knowledge of the interiors of fault locators. Consequently, the nine chapters are organised according to the design of different locators. The authors do not simply refer the reader to manufacturers documentation, but instead have compiled detailed information to allow for in-depth comparison. Fault Location on Power Lines describes basic algorithms used in fault locators, focusing on fault location on overhead transmission lines, but also covering fault location in distribution networks. An application of artificial intelligence in this field is also presented, to help the reader to understand all aspects of fault location on overhead lines, including both the design and application standpoints. Professional engineers, researchers, and postgraduate and undergraduate students will find Fault Location on Power Lines a valuable resource, which enables them to reproduce complete algorithms of digital fault locators in their basic forms.